MicroRNA-877-5p Inhibits Cell Progression by Targeting FOXM1 in Lung Cancer - Zhiguang Liu; Xinlian Wang; Liqiang Cao; Xiaowei Yin; Qian Zhang; Lan Wang (Canadian Respiratory Journal)
Background. Many researches revealed that microRNAs (miRNAs) function as potential oncogene or tumor suppressor gene. As an antioncogene, miR-877-5p was reduced in many tumors. Objective. This research aimed to explore the biological role and mechanisms of miR-877-5p, which may help patients with non-small-cell lung cancer (NSCLC) find effective therapeutic targets. Methods. The downstream targets of miR-877-5p were predicted by Bioinformatics software. RT-qPCR and western blot were employed to analyze the gene levels. The impacts of miR-877-5p and FOXM1 were assessed by cell function experiments. Results. The miR-877-5p was reduced in NSCLC. In addition to this, it also inhibited cell progression of NSCLC cells in vitro. Moreover, the upregulation of FOXM1 expression restored the inhibitory effect of enhancement of miR-877-5p. Conclusions. Taken together, miR-877-5p inhibited cell progression by directly targeting FOXM1, which may provide potential biomarkers for targeted therapy of NSCLC.